Design for BIO4GS Module’s Element Based on Experts’ Consensus: Fuzzy Delphi Method Application - Salleh, Wan Nasriha Wan Mohamed; Ahmad, Che Nidzam Che (CENTRAL ASIA AND THE CAUCASUS, 2022)
The BIO4GS Module is a teaching and learning module that applies gamification to enhance students’ engagement and motivation towards learning Biology. This study aimed to analyse experts’ opinions and consensus on the element of BIO4GS Module. This study employed the Fuzzy Delphi Method (FDM) by using a seven-point Likert scale to collect responses of 23 experts in various backgrounds and fields of education. The experts involved in this study were selected using the purposive sampling method. A Design Module Questionnaire was given to the experts for evaluation. Data were analysed using the triangular Fuzzy numbering (Triangular Fuzzy Number) and the Fuzzy evaluation process (defuzzification). The results showed that the experts’ agreement exceeded 75%, the overall value of the threshold (d) ≤ 0.2, and an Amax value exceeds the value of α-cut = 0.5. This indicated that all items in the questionnaire met the requirements required in the Triangular Fuzzy Number and the Fuzzy evaluation process (defuzzification). The findings showed that experts reached a consensus with the elements of gamification and educational game components. Therefore, all these elements can be used not only to design and develop the BIO4GS Modules but also as a reference in the development of other modules.